High incidence of tuberculosis, low sensitivity of current diagnostic scheme and prolonged culture positivity in four Colombian prisons. A cohort study (2013)
ABSTRACT: Objective: To determine the incidence of pulmonary tuberculosis (TB) in inmates, factors associated with TB, and the time to sputum smear and culture conversion during TB treatment. Methods: Prospective cohort study. All prisoners with respiratory symptoms (RS) of any duration were evaluated. After participants signed consent forms, we collected three spontaneous sputum samples on consecutive days. We performed auramine-rhodamine staining, culturing with the thin-layer agar method, Löwestein-Jensen medium and MGIT, susceptibility testing for first-line drugs; and HIV testing. TB cases were followed, and the times to smear and culture conversion to negative were evaluated. Results: Of 9,507 prisoners held in four prisons between April/30/2010 and April/30/2012, among them 4,463 were screened, 1,305 were evaluated for TB because of the lower RS of any duration, and 72 were diagnosed with TB. The annual incidence was 505 cases/100,000 prisoners. Among TB cases, the median age was 30 years, 25% had <15 days of cough, 12.5% had a history of prior TB, and 40.3% had prior contact with a TB case. TB-HIV coinfection was diagnosed in three cases. History of prior TB, contact with a TB case, and being underweight were risk factors associated with TB. Overweight was a protective factor. Almost a quarter of TB cases were detected only by culture; three cases were isoniazid resistant, and two resistant to streptomycin. The median times to culture conversion was 59 days, and smear conversion was 33. Conclusions: The TB incidence in prisons is 20 times higher than in the general Colombian population. TB should be considered in inmates with lower RS of any duration. Our data demonstrate that patients receiving adequate antiTB treatment remain infectious for prolonged periods. These findings suggest that current recommendations regarding isolation of prisoners with TB should be reconsidered, and suggest the need for mycobacterial cultures during follow-up.